A PAX3/BRN2 rheostat controls the dynamics of BRAF mediated MITF regulation in MITFhigh/AXLlow melanoma. (19th October 2018) - Smith, Michael P.; Rana, Sareena; Ferguson, Jennifer; Rowling, Emily J.; Flaherty, Keith T.; Wargo, Jennifer A.; Marais, Richard; Wellbrock, Claudia
Abstract: The BRAF kinase and the MAPK pathway are targets of current melanoma therapies. However, MAPK pathway inhibition results in dynamic changes of downstream targets that can counteract inhibitor‐action not only in during treatment, but also in acquired resistant tumours. One such dynamic change involves the expression of the transcription factor MITF, a crucial regulator of cell survival and proliferation in untreated as well as drug‐addicted acquired resistant melanoma. Tight control over MITF expression levels is required for optimal melanoma growth, and while it is well established that the MAPK pathway regulates MITF expression, the actual mechanism is insufficiently understood. We reveal here, how BRAF through action on the transcription factors BRN2 and PAX3 executes control over the regulation of MITF expression in a manner that allows for considerable plasticity. This plasticity provides robustness to the BRAF mediated MITF regulation and explains the dynamics in MITF expression that are observed in patients in response to MAPK inhibitor therapy.